Exogenous abscisic acid promotes the nitrogen use efficiency of Brassica napus by increasing nitrogen remobilization in the leaves. (8th November 2017) - Han, Yong-Liang; Liao, Jia-Yuan; Yu, Yin; Song, Hai-Xing; Rong, Nan; Guan, Chun-Yun; Lepo, Joe Eugene; Ismail, Abdelbagi M.; Zhang, Zhen-Hua
ABSTRACT: The effect of exogenous abscisic acid (ABA) on the nitrogen use efficiency (NUE) of Brassica napus was studied by pot experiments using ABA (1 mg L −1 ) daubed on the leaves at the early siliquing stage. The results showed that activities of proteases and glutamine synthetase (GS) were significantly promoted by the ABA treatment, which increased the capacity of degradation of foliar proteins and biosynthesis of glutamine (N-transport compounds), both of which promote decreased N in leaves of the ABA treatment. L-glutamine, other free amino acids, and soluble sugar content in the phloem sap of the ABA treatment were significantly higher than those of the control. A 15 N label trial showed that more 15 N was distributed from leaves to the grain by the ABA treatment, which resulted in a significantly higher NUE in the ABA treatment relative to the control.